PENINGKATAN LITERASI MASYARAKAT DALAM PENCEGAHAN STUNTING DI DESA SIRNAJAYA - Kartikasari, Wulan; Rokaya Az-Zahra, Descha; Dewi Cahyati, Ari; Putra, Purnama (Universitas Islam 45 Bekasi, 2024)
Stunting is a serious health, social and economic problem in Indonesia, as it can reduce the quality of human resources. Stunting is a condition where children experience suboptimal growth and development due to chronic malnutrition from the womb until the age of 2 years. The purpose of community service activities in the stunting prevention program in Sirnajaya Village is to educate the community about the importance of balanced nutrition and proper child care to prevent stunting and change community behaviour related to diet, health care, and healthy lifestyles to better support optimal growth and development of children. In the implementation of community service through this KKN activity, we used a community education method, where the author conducted counselling aimed at increasing community understanding and awareness of stunting. The result of the community service activity is an increase in parents' insight into the importance of child nutrition so that it can prevent stunting in children and families.